Gestão da produção orientado pelo desempenho: um estudo de caso numa fábrica de componentes eletroeletrônicos - Candido, Jhoiny (2017)
The competitive environment present in most markets and the constant technological changes pressure companies to develop and use management tools and methods aimed at the full utilization of installed facilities, whether equipment or people, to reduce manufacturing costs. This way, the management of production oriented by the analysis of the efficiency of the production systems has become a relevant and mandatory topic in the maintenance of profitability in the context of industrial companies. One tool that stands out for its simplicity is the Global Operating Income Index (IROG), which is usually applied to the measurement of the degree in the machinery utilization, and also played an important role as an indicator capable of demonstrating the real use of human resources. IROG provides a clear view of performance against what is expected from an installed resource and provides data for a critical analysis to maximize the amount produced per worker versus the total availability of the resource. This article proposes an analysis about the management of resources in purely operational environments seeking to establish correlations between the forms of management and measurement of performance against the established objectives. This work is classified as an applied nature, as it aims to discuss the interaction between the operational indexes in a company of electro-electronic components installed in the north of Santa Catarina. It is an explanatory - descriptive research aiming to expose the analyzed factors and to point out the control conditions existing in the method that are compatible with the practices of the company. The case studied was based on the bibliographic survey of Performance Measurement, Productivity, Workplace Management and Restriction Theory. The main results obtained were the greater involvement of the operational team in the analysis and decision making, a better level of productivity and the optimization of the portion of the direct labor force due to suitable sizing of the necessary resource.